Who is reducing their material consumption and why? A cross-cultural analysis of dematerialization behaviours. (1st May 2017) - Whitmarsh, Lorraine; Capstick, Stuart; Nash, Nicholas
Abstract : The environmental and economic imperatives to dematerialize economies, or 'do more with less', have been established for some years. Yet, to date, little is known about the personal drivers associated with dematerializing. This paper explores the prevalence and profile of those who are taking action to reduce consumption in different cultural contexts (UK and Brazil) and considers influences on dematerialization behaviours. We find that exemplar behaviours (avoiding buying new things and avoiding packaging) are far less common than archetypal environmental behaviours (e.g. recycling), but also that cultural context is important (Brazilians are more likely to reduce their material consumption than people in the UK). We also find that the two dematerialization behaviours are associated with different pro-environmental actions (more radical action versus green consumption, respectively); and have distinct, but overlapping, psychological (e.g. identity) and socio-demographic (e.g. education) predictors. Comparing a more traditional value-identity model of pro-environmental behaviour with a motivation-based (self-determination) model, we find that the latter explains somewhat more variance than the former. However, overall, little variance is explained, suggesting that additional factors at the personal and structural levels are important for determining these consumption behaviours. We conclude by outlining policy implications and avenues for further research. This article is part of the themed issue 'Material demand reduction'.